Older People in Crisis: Yemen’s Urgent Call for Humanitarian Assistance - Shamsan, Alaa Ahmed Mohammed (Magyar Gerontológia, 2024)
The conflict in Yemen which has been ongoing for ten years led to one of the worst humanitarian crises worldwide. While the attention is given more to the general population, there are many unique challenges focusing on vulnerable elderly people face that remain unnoticed.